GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 11 Dec 2019, 23:14 ### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

#### Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.  # Let <x, y, z> denote 2x + yz. Moreover, let x + y = 2p, y + z = 2q, z

Author Message
TAGS:

### Hide Tags

Math Revolution GMAT Instructor V
Joined: 16 Aug 2015
Posts: 8251
GMAT 1: 760 Q51 V42 GPA: 3.82
Let <x, y, z> denote 2x + yz. Moreover, let x + y = 2p, y + z = 2q, z  [#permalink]

### Show Tags 00:00

Difficulty:   5% (low)

Question Stats: 100% (02:52) correct 0% (00:00) wrong based on 16 sessions

### HideShow timer Statistics

[GMAT math practice question]

Let $$<x, y, z>$$ denote $$2x + yz$$. Moreover, let $$x + y = 2p, y + z = 2q, z + x = 2r, xy = a, yz = b$$ and $$zx = c.$$

How can $$<x, 3y, z> + <y, 3z, x> + <z. 3x, y>$$ be written in terms of $$a, b, c, p, q$$ and $$r$$?

A. $$p+q+r+a+b+c$$

B. $$2(p+q+r+a+b+c)$$

C. $$2(p+q+r+a+b+c)$$

D. $$2(p+q+r)+3(a+b+c)$$

E. $$3(p+q+r)+2(a+b+c)$$

_________________
CrackVerbal Quant Expert G
Joined: 12 Apr 2019
Posts: 318
Re: Let <x, y, z> denote 2x + yz. Moreover, let x + y = 2p, y + z = 2q, z  [#permalink]

### Show Tags

From the question stem, we can estimate that this is a cyclic expression. A cyclic expression is where the order of the terms follow a cyclic pattern. This can be understood better when we break down the question stem.

It’s given that <x,y,z> = 2x + yz. In layman terms, this means, whatever the first number is has to be multiplied by 2 and added to the product of the other two numbers.

Using this, we get <x,3y,z> = 2x + 3yz = 2x + 3b {because yz = b}. Let this be equation 1.

<y,3z,x> = 2y + 3zx = 2y + 3c { notice how the positions of the variables have shifted by one place to the left and that is why I preferred to call them cyclic}. Let this be equation 2.

<z,3x,y> = 2z + 3xy = 2z + 3a. {notice how the last terms are 3b, 3c and 3a, which are cyclic as well}. Let this be equation 3

Adding the three equations, we have,
<x,3y,z> + <y,3z,x> + <z,3x,y> = 2x + 2y + 2z + 3(a+b+c). Let’s call this equation 4.

We also know that x + y = 2p, y + z = 2q, z + x = 2r; adding the equations, we get,
2x + 2y + 2z = 2(p+q+r). Substituting this value in equation 4, we obtain our required answer as 2(p+q+r) + 3(a+b+c).

The correct answer option is D.
Hope that helps!
_________________
Math Revolution GMAT Instructor V
Joined: 16 Aug 2015
Posts: 8251
GMAT 1: 760 Q51 V42 GPA: 3.82
Re: Let <x, y, z> denote 2x + yz. Moreover, let x + y = 2p, y + z = 2q, z  [#permalink]

### Show Tags

=>

When we add $$x + y = 2p, y + z = 2q,$$ and $$z + x = 2r$$, we have $$x + y + y + z + z + x = 2p + 2q + 2r, 2(x + y + z) = 2(p + q + r)$$ or $$x + y + z = p + q + r.$$

When we add $$xy = a, yz = b$$ and $$zx = c,$$ we have $$xy + yz + zx = a + b + c.$$

$$<x, 3y, z> = 2x + 3yz, <y, 3z, x> = 2y + 3zx, <z, 3x, y> = 2z + 3xy.$$

Then $$<x, 3y, z> + <y, 3z, x> + <z, 3x, y> = 2x + 3yz + 2y + 3zx + 2z + 3xy = 2(x +y + z) + 3(xy + yz + zx) = 2(p + q + r) + 3(a + b + c).$$

_________________ Re: Let <x, y, z> denote 2x + yz. Moreover, let x + y = 2p, y + z = 2q, z   [#permalink] 24 Nov 2019, 19:22
Display posts from previous: Sort by

# Let <x, y, z> denote 2x + yz. Moreover, let x + y = 2p, y + z = 2q, z  